Pelatihan Pengembangan Kompetensi dan Competitiveness Siswa Di Bidang Ilmu Sosial - Arini Wildaniyati; Mutmainah Mutmainah; Mintarti Indartini (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Competence and skills of students must continue to be honed in order to further develop and be competitive. In addition, their competitive spirit must also be grown so that their spirit of achievement will automatically emerge and be able to compete at the national level. Through this training, it is hoped that students will be able to develop their competence and grow their competitive spirit. This training is carried out by enriching social science questions and motivating students by informing them of the benefits that will be obtained in achieving. This training activity was attended by Grade 9 Social Sciences students with great enthusiasm. This can be seen from the results of their learning evaluation showing that most of the scores obtained were very satisfying. In addition, it can be seen from the way students pay attention and their activeness in class.